The founding father of biotechnology: Károly (Karl) Ereky - Fári, M. G.; Kralovánszky, U. P. (International Journal of Horticultural Science, 2006)
Nowdays it is generally expressed opinion of the leading scientific circles that the purposefully planned biotechnological actions of the 21st century will be indispensable of realizing the sustainable technical development in the supplementation of the increasing population, especially those who suffer privation, thus the long-distance interests of mankind will be met without impairing the world’s ecological integrity. In 1989 Robert Bud gave account of the fact that the father of the term "biotechnology" was the Hungarian agricultural engineer, Karl Ereky. Recently, we have explored and found some important biographical sources and scientific documents which had been published by Károly (Karl) Ereky, the which, however, have already been forgotten. This article expands on that more contextual treatment to explore the man and his doctrine. It draws upon Hungarian and private sources as well as on German publications.